2012
DOI: 10.3762/bjoc.8.99
|View full text |Cite
|
Sign up to set email alerts
|

meta-Oligoazobiphenyls – synthesis via site-selective Mills reaction and photochemical properties

Abstract: SummaryThe investigation of multi-photochromic compounds constitutes a great challenge, not only from a synthetic point of view, but also with respect to the analysis of the photochemical properties. In this context we designed a novel strategy to access meta-oligoazobiphenyls via site-selective Mills reaction and Suzuki cross-coupling in a highly efficient iterative way. Photochemical examination of the resulting monomeric and oligomeric azo compounds revealed that the overall degree of switching was independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Among peracetic acid, meta -chloroperoxybenzoic acid ( m CPBA), and magnesium monoperoxyphthalate (MMPP), we found that m CPBA performed best. The use of mCPBA to prepare nitrosobenzenes from anilines is well precedented . A screen of solvent mixtures revealed that diluting acetic acid with DCM or toluene resulted in a further increased yield, although a sizable fraction of acetic acid was necessary for optimal results.…”
Section: Resultsmentioning
confidence: 99%
“…Among peracetic acid, meta -chloroperoxybenzoic acid ( m CPBA), and magnesium monoperoxyphthalate (MMPP), we found that m CPBA performed best. The use of mCPBA to prepare nitrosobenzenes from anilines is well precedented . A screen of solvent mixtures revealed that diluting acetic acid with DCM or toluene resulted in a further increased yield, although a sizable fraction of acetic acid was necessary for optimal results.…”
Section: Resultsmentioning
confidence: 99%
“…While in this work static quantum chemical calculations are sufficient to demonstrate the concept of meta-connectivity and the computational design of a first triple-photoswitch based on azobenzene, in general nuclear quantum dynamics are required to study the efficiency of photoswitching and to determine timescales and relevant loss channels. In the future we plan to synthesize and spectroscopically investigate the suggested meta -trisazobenzene derivatives in analogy to previous works 4951. This work indeed paves the way for future development of selectively photoswitchable control systems being used in advanced materials and nano-electronic devices.…”
Section: Discussionmentioning
confidence: 72%
“…However, the simplest way for the symmetrical oxidative coupling is to use the air oxygen [ 41 , 42 , 43 , 44 ]. Mills reaction allows also oxidative coupling from anilines, but leading to unsymmetrical azobenzenes [ 45 , 46 , 47 , 48 , 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%